Connect-four: genomic analyses of regenerating stem cells identifies zygotic Dux factors as tumor initiators. (4th March 2019) - Preussner, Jens; Zhong, Jiasheng; Looso, Mario; Braun, Thomas; Kim, Johnny
ABSTRACT: How, if and in which cell types embryonic gene expression programs are elicited to induce tumor formation remains poorly understood. Through genomic analyses of regenerating, p53 deficient muscle stem cells we identified various oncogenomic amplifications, including but not limited to, the zygotic transcription factor Duxbl / DUXB to initiate tumorigenic transformation.